Pengabdian Penyediaan Tandon Air Bersih Portable Sebagai Solusi Darurat Kebutuhan Air Masyarakat Pascabencana Aceh Tamiang - Fairus; Afrah Junita; Agus Putra AS (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This Community Service activity was carried out in response to the flash flood disaster in Simpang Lhee Village, Manyak Payed District, Aceh Tamiang Regency, which caused a clean water crisis due to the contamination of community water sources. The objective of the activity was to provide access to clean water through the application of appropriate technology in the form of portable clean water tanks and to increase community preparedness for disaster emergencies. The implementation method used a participatory approach through the stages of socialization, technology application, mentoring, and evaluation. The results of the activity showed that the installation of portable clean water tanks with a capacity of approximately 1,000 liters was able to increase community access to clean water in a more equitable and sustainable manner. This program also increased community knowledge about clean and healthy living behaviors (PHBS), reduced the risk of disease due to the use of unsafe water, and reduced community expenditure. In addition, community participation in clean water management and preparedness for clean water crises also increased. In conclusion, the provision of portable clean water tanks is an effective and sustainable solution to address the post-disaster clean water crisis while strengthening community resilience.